2003
DOI: 10.1183/09031936.03.00033702
|View full text |Cite
|
Sign up to set email alerts
|

Passive smoking and respiratory symptoms in the FinEsS Study

Abstract: The aim of the present study was to examine the relationship between reported environmental tobacco smoke (ETS) exposure and respiratory symptoms.In 1996, a postal questionnaire was randomly distributed in three areas of Estonia to a population-based sample, of which 4,995 females and 1,822 males had never smoked. The main outcome measures were current respiratory symptoms and the amount of reported ETS exposure outside the home.ETS exposure at home was more common in females (31% versus 19%), while exposure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
75
1
4

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 28 publications
(31 reference statements)
11
75
1
4
Order By: Relevance
“…This found that the prevalence of respiratory symptoms remained higher in ex-smokers for many years compared with nonsmokers [29]. Passive smoking is associated with asthma and respiratory symptoms [17,30], and it is disappointing that data about passive smoking were not available. However, smoking was more common among manual workers, which is why passive smoking was probably also more common in this group and could contribute to the increased risk of asthma and respiratory symptoms.…”
Section: Socio-economic Status and Asthmamentioning
confidence: 95%
See 1 more Smart Citation
“…This found that the prevalence of respiratory symptoms remained higher in ex-smokers for many years compared with nonsmokers [29]. Passive smoking is associated with asthma and respiratory symptoms [17,30], and it is disappointing that data about passive smoking were not available. However, smoking was more common among manual workers, which is why passive smoking was probably also more common in this group and could contribute to the increased risk of asthma and respiratory symptoms.…”
Section: Socio-economic Status and Asthmamentioning
confidence: 95%
“…The questionnaire was developed from a revised version [15] of the UK Medical Research Council questionnaire [16], and has been used in other Swedish and international studies [17]. The questions about respiratory symptoms and diseases included the following: recurrent wheeze, attacks of shortness of breath, long-standing cough, sputum production, chronic productive cough, asthma, allergic rhinitis, chronic bronchitis or emphysema, and use of asthma medicines.…”
Section: Methodsmentioning
confidence: 99%
“…
We read with interest the paper by LARSSON et al [1] in which they reported in a large population-based sample of nonsmokers that respiratory symptoms were related to environmental tobacco smoke (ETS). They gave special consideration to respiratory symptoms triggered by a variety of lower airway irritants and they showed for these symptoms that the relation was stronger in females than in males.
…”
mentioning
confidence: 72%
“…Una proporción de casos de EPOC ocurre en personas que no han fumado nunca. Entre personas no fumadoras (54) el tabaquismo pasivo es un factor de riesgo para el desarrollo de la EPOC (55)(56)(57)(58). Un estudio elaborado en niños de entre 6 y 18 años gallegos, donde el 56% de ellos estaban expuestos al humo del tabaco de alguno de sus progenitores, mostro un 75 % tenían reducida la capacidad espiratoria forzada (FEF), con el efecto obstructivo en la vía distal, tal y como ocurre en los pacientes fumadores activos (59).…”
Section: Gravedad De Las Exacerbacionesunclassified
“…Existen investigaciones que afirman que la exposición al polvo ambiental y humos en países en vías de desarrollo o desarrollados (54)(55)(56)(58)(59)(60)(61)(62)(63)(64)68), como el ozono, las partículas en suspensión, el monóxido de carbono (CO), el dióxido de sulfuro (SO 2 ) , el dióxido de nitrógeno (NO 2 ), otros gases (54), materiales industriales, partículas procedentes de la minería y la combustión, productos La educación terapéutica en los pacientes con EPOC químicos agrícolas, el humo de los cigarros presentes en la contaminación atmosférica, asociados al tráfico rodado, es un factor de predisposición a las exacerbaciones (69). Sin embargo existe controversia en cuanto a su relación como factor de causa directa de la enfermedad (54).…”
Section:  Contaminación Atmosféricaunclassified